Efektivitas Penggunaan Media Audio Visual untuk Meningkatkan Kemampuan Mengenal Lambang Bilangan 1-10 Pada Peserta Didik Tunagrahita Kelas III di SLB Negeri Kota Radja Kupang (Indo-MathEdu Intellectuals Journal, 2025)
The background of this study is that students with mild intellectual disabilities still experience difficulties in recognizing number symbols 1-10. Although they have a normal age, students with intellectual disabilities have a mental age below their actual age, so learning media tailored to their characteristics and mental age is needed in learning. This study aims to improve the ability to recognize number symbols 1-10 through the use of audiovisual media. The method used is Classroom Action Research (CAR) with a quantitative descriptive approach based on Kurt Lewin's model, which includes four stages: planning, action, observation, and reflection. The research subjects were 4 students with mild intellectual disabilities in Grade III at SDLB Negeri Kota Radja Kupang. Data were collected through student observation sheets and student learning outcome tests. The research results show an increase in the ability to recognize number symbols from an average of 50% in Cycle I to 75% in Cycle II. Thus, it can be concluded that the use of audiovisual media is proven effective in improving the ability to recognize number symbols 1-10 for students with mild intellectual disabilities in grade III at SLB Negeri Kota Radja Kupang